LI-Yorke sensitivity and other concepts of chaos - Kolyada, S. F. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We give a survey of the theory of chaos for topological dynamical systems defined by continuous maps on compact metric spaces.